Perceived Image and Service Quality Affecting Thai Tourists’ Loyalty of Three - Star Hotels at Hatyai District in Songkhla Province - Limwattana, Pimjai; Sirichote, Orachan; Noourai, Nitchakarn (Parichart Journal, 2020)
This research article aimed 1) to examine perceived image affecting Thai tourists’ loyalty of three - star hotels at hatyai district in songkhla province and 2) to investigate the perceived service quality affecting Thai tourists’ loyalty of three - star hotels at hatyai district in songkhla province. The sample samplings was conducted from four hundred Thai tourists using the services of three - star hotels at hatyai district in songkhla province. A questionnaire was employed as the data collection instrument. The statistics for data analysis were frequency, percentage, mean, standard deviation, and Multiple Regression Analysis. The results indicated that the perceived image, location, security, and social responsibility positively affecting on Thai tourists’ loyalty of three - star hotels at the overall were statistically significant at .05 level and the perceived service quality in objectiveness, confidence, caring, and reaction positively affecting Thai tourists’ loyalty of three - star hotels at the overall were statistically significant at .05 level. Meanwhile, the reliability did not affect Thai tourists’ loyalty to three - star hotels at the overall.